Peace Unwanted? – The Frozen Conflict of Nagorno-Karabakh Revisited - Pia Ferner (Institute of International Studies, 2015)
More than twenty years after the ceasefire agreement has been signed between Armenia and Azerbaijan, little has been reached in resolving the dispute over Nagorno-Karabakh. This paper aims to provide insight into political dimensions of the conflict combining a geopolitical perspective with a perspective of local dynamics on the ground. Analyzing contributing factors to the lack of progress in the durable settlement of the conflict over Nagorno-Karabakh provides an outlook on possibilities for a peaceful settlement of the dispute, which is of high relevance from a humanitarian perspective. The current positions of international actors contributing to the stalemate, as well as a lack of influential involvement of the civil society in the region provide little reason to believe significant change for a peaceful settlement of the conflict will be made in the near future. Increased transparency and improved communication are needed to provide opportunities for a peaceful change.This paper is primarily based on desk research, with additional insights gained from a research stay, and was issued as a contribution to Indonesian Humanitarian Action Forum. It is seen as an opportunity to shed light on an often forgotten conflict which poses strong humanitarian concerns due to a large number of IDPs (Internally Displaced Person) and continued landmine contamination hindering development.